THE EFFECT OF POPULATION ADMINISTRATIVE INFORMATION SYSTEM MANAGEMENT (PIAK) ON THE QUALITY OF FAMILY CARD SERVICE AT THE SERVICE POPULATION AND CIVIL REGISTRATION OF BARRU DISTRICT - Hj.Aidah; A.Pananrangi. M (Sean Institute, 2023)
This study aims to find out: How does system processing affect population administration information (PIAK) on the quality of family card (KK) services. And what factors support and hinder the processing of information systems population administration (PIAK) and quality of family card (KK) services. Data source obtained by means of Surveys, Interviews, Observations, Questionnaires. Data analysis Using Validity. The results of this study indicate that the level of the regression coefficient variable X of 1579.144; meaning that if X is increased by 1%, then the value of card service quality family (KK) will experience an increase of 1579.144 assuming that the variable other independent value is fixed. Because the value of the regression coefficient is positive (+) then with thus it can be said that the processing of population administration information systems (X) significant effect on the quality of family card services (Y). so the equation the regression is Y = -165,845 + 1579,144. This proves that the processing system Population administration information has a significant effect on the quality of card services family. The factors that support and hinder the processing of the system population administration information (PIAK) and quality of family card (KK) services, - Supporting factors include (the support of the new city government, cooperation, adequate facilities and infrastructure), - Inhibiting factors which include (limited resources human resources, low public awareness regarding population administration, network internet problems / no connectivity).